2002
DOI: 10.1053/bbmt.2002.v8.pm12374453
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of safety and pharmacokinetics of administering intravenous busulfan in a twice-daily or daily schedule to patients with advanced hematologic malignant disease undergoing stem cell transplantation

Abstract: Intravenous busulfan (i.v. BU) has demonstrated safety when administered at 0.8 mg/kg per dose i.v. every 6 hours x 16 doses. We evaluated the safety and pharmacokinetics (PK) of giving the same total daily i.v. BU dose (3.2 mg/kg) either divided as a twice-daily infusion or as a single infusion to patients undergoing hematopoietic stem cell transplantation (HSCT). Twelve patients with hematologic malignant disease were treated; 7 patients had non-Hodgkin's lymphoma, 4 patients had acute myeloid leukemia, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 20 publications
2
40
0
Order By: Relevance
“…In 90% of the children, engraftment was established, which is in accordance with previous reports. 14,18 The pharmacokinetic parameters reported in this study are in the same range as previously seen in studies with both oral 19,20 and intravenous dosing of Bu in children. 7,15,16 Based on the present and previously reported data, it is clear that the excretion of Bu is age and weight dependent.…”
Section: Bu Pharmacokineticssupporting
confidence: 74%
See 1 more Smart Citation
“…In 90% of the children, engraftment was established, which is in accordance with previous reports. 14,18 The pharmacokinetic parameters reported in this study are in the same range as previously seen in studies with both oral 19,20 and intravenous dosing of Bu in children. 7,15,16 Based on the present and previously reported data, it is clear that the excretion of Bu is age and weight dependent.…”
Section: Bu Pharmacokineticssupporting
confidence: 74%
“…Total AUCs were estimated from clearance calculated for the first dose and the total dosage, since in previous studies it was found that the AUC on day 4 was equal to AUC on day 1. 7,14 The total dosage was calculated for each individual patient taking all dose adjustments into consideration. We were able to determine the AUC again after dose adjustment (on the second day of Bu infusion) in nine patients.…”
Section: Pharmacokinetics and Statistical Analysismentioning
confidence: 99%
“…BU. 4,8,10,[13][14][15][16][17][18] Nevertheless, the clinical outcomes and the study of pharmacokinetics (PK) of once-daily i.v. BU in Asian adult populations are still scanty.…”
Section: Introductionmentioning
confidence: 99%
“…3 A mean AUC of 1002 mM min per dose was reported for this dosing regimen. Schedules of 1.6 mg/kg every 12 h or 3.2 mg/kg every 24 h 4,5 were evaluated as alternatives to the every 6 h regimen. The efficacy and predictable blood concentrations from 3.2 mg/kg once daily dosing were further validated in other studies.…”
Section: Introductionmentioning
confidence: 99%